2007
DOI: 10.1590/s0100-40422007000800024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oil from Aeolanthus suaveolens Mart. ex Spreng

Abstract: The essential oils from leaves (sample A) and flowers (sample B) of Aeolanthus suaveolens Mart. ex Spreng were obtained by hydrodistillation and analyzed by GC, GC-MS, and chiral phase gas chromatography (CPGC). Six compounds have been identified from the essential oils, representing ca 94.3 and 93% of the oils corresponding to samples A and B, respectively. The major constituents of samples A and B essential oils were respectively, linalool (34.2%/34.9%), (-)-massoialactone (25.9%/17.0%) and (E)-beta-farnesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
2
9
1
1
Order By: Relevance
“…These results corroborate other reports 16 , which obtained a yield substantially close (0.07%). However, there is a difference with the results from other studies with a yield of 1.3% 29 . The variation observed in the extraction yield could be due to many factors, including the effect of the climate variation, the nature of the geographical site, the quality of the soil, and the harvesting period, which could impact the quality and amount of the volatile fraction.…”
Section: Extraction Yields Of the Essential Oil And Solvent Extractscontrasting
confidence: 91%
“…These results corroborate other reports 16 , which obtained a yield substantially close (0.07%). However, there is a difference with the results from other studies with a yield of 1.3% 29 . The variation observed in the extraction yield could be due to many factors, including the effect of the climate variation, the nature of the geographical site, the quality of the soil, and the harvesting period, which could impact the quality and amount of the volatile fraction.…”
Section: Extraction Yields Of the Essential Oil And Solvent Extractscontrasting
confidence: 91%
“…Studies by Simionatto et al [34] with isolated compounds from A . suaveolens analyzed by bioautography showed that the lactone monoterpene massoialactona exhibited excellent antibacterial property to Salmonella Setubal and Bacillus subtilis microorganisms, being active in the minimum concentration that was tested (3.125 μg.mL -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…suaveolens , where the synergistic effect of monoterpene compounds and sesquiterpene appears to potentiate the toxicity against the larvae of A . salina , the antimicrobial isolates proved to be the most isolated active compounds (massoialactona) of all the essential oil components [34]. However, it is important to note that synergistic or antagonistic effects should not be excluded from antimicrobial activity [37].…”
Section: Resultsmentioning
confidence: 99%
“…Although many of the monoterpenes have not been previously evaluated on yeasts, antibacterial and antifungal activity of essential oils with a high concentration of the monoterpenes included in the present work have been reported. For example, Mentha spicata essential oil with high content of carvone (51.7%) and carveol (24.35%), and the essential oil of Aeolanthus suaveolens with a high concentration of linalool (34.2 to 34.9%) exhibited antimicrobial activity against bacteria and fungi (Hussain et al., 2010; Simionatto et al., 2007), and commercial essential oils of cinnamon, oregano, marigold, clove, and laurel oil inhibited the growth of several food yeasts, including S. cerevisiae , with MIC values ranging from 7.8 to 500 mg/L (Çoskun et al., 2016). Eventual discrepancies of antifungal activities of essential oils or terpene on yeasts or fungi have been attributed to differences in experimental conditions and extraction procedures, as well as microbial species and strains used in each work (Bakkali et al., 2008; Cowan, 1999).…”
Section: Resultsmentioning
confidence: 99%